Effects of intracameral ascorbic acid on the corneal endothelium of dogs undergoing phacoemulsification - M. Padua, Ivan R. [UNESP]; P. Valdetaro, Gisele [UNESP]; B. Lima, Tiago [UNESP]; K. Kobashigawa, Karina [UNESP]; E. S. Silva, Paloma [UNESP]; Aldrovani, Marcela [UNESP]; M. Padua, Pedro P.; Laus, Jose L. [UNESP] (Wiley, 2018)
Objective: Cataracts are the most common ocular disorder in dogs. Phacoemulsification is the preferred treatment method among ophthalmologists, but the cellularity of the endothelium must be considered for its success, as endothelial lesions may produce permanent corneal decompensation. The objective of this study was to evaluate the effects of intracameral ascorbic acid, a known antioxidant, on the corneal endothelium of dogs undergoing phacoemulsification. Animal studied: In all, 40 eyes from 20 dogs, males and females from 7 to 12 years of age, were assessed for mature cataracts. Procedures: Two groups were formed (n = 20): Group 1 (G1) received a balanced salt solution (BSS), whereas Group 2 (G2) received sterile ascorbic acid diluted in a BSS, at a final concentration of 0.001 m ascorbic acid. The corneal endothelium was assessed via non-contact specular microscopy at multiple time points before and after phacoemulsification. Cell density (cells/mm2) and area (mm2), corneal thickness (mm), hexagonality, and the coefficient of variation of cell size were all assessed. P values equal to or less than 0.05 were considered significant. Results: With respect to the density of endothelial cells, both groups showed losses, but they were less severe in G2. There were no differences in corneal thickness. Hexagonality decreased significantly in the postoperative period in G1. Also in G1, the coefficient of variation of cell size increased significantly. Conclusion: According to the results obtained, ascorbic acid minimizes cellular losses in the corneal endothelium.
Keywords: ascorbic acid; cataract; cornea; dog; endothelial cells; phacoemulsification